Computer vision approaches for automatic inspection of wire bonding of semiconductor devices - Lim, Han Ooi. (2009)
There is a demand in the semiconductor industries for geometry inspection of the wire bonding balls on an integrated circuit. This is currently being carried out manually by human operator with the aid of a 500X magnification microscope. This thesis shows that simple image processing technique can be applied to perform the inspection automatically. The operators need only to place the lead frame of the integrated circuit at a reference location on the X-Y table and press a button on the keyboard. The system will take care of the alignment, focusing, height measurement and diameter measurement of the bonding balls on the integrated circuit.